Digenesis: Flipbook-Based Teaching Materials on Civics Education for Grade IV Elementary School - Pramestya, Denty; Witanto, Yuli (Universitas Pendidikan Ganesha, 2024)
The use of teaching materials that are less interactive and do not maximize the use of technology is a problem that can affect student learning outcomes. This study aims to produce digital teaching materials based on flipbook in Civic Education class IV elementary school subjects that are practical, feasible, effective, and can improve student learning outcomes. The implication of this research is that the learning process becomes more creative and innovative because of the digital teaching materials that involve technology in its use. The research method used in this research is the Research & Development (R&D) method which was developed with the ADDIE model. The subjects involved included 1 material expert, 1 media expert, 1 teacher, and 22 fourth grade students. The data collection techniques used are test techniques in the form of pretests and post-tests, and non-test techniques in the form of observation results, teacher interviews, and questionnaires. Meanwhile, the data analysis technique was carried out by practicality test and N-Gain test. The results of the validation of teaching materials by material experts of 90,6% and media experts of 95% show that the teaching materials